In-situ gelling liquid crystal mucoadhesive vehicle for curcumin buccal administration and its potential application in the treatment of oral candidiasis - Fonseca-Santos, Bruno [UNESP]; Bonifácio, Bruna Vidal [UNESP]; Baub, Taís Maria [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Chorilli, Marlus [UNESP] (American Scientific Publishers, 2019)
The treatments of oral candidiasis involve azole-based antifungals; however, the fungal resistance of these drug compounds has been detected in worldwide. Therefore, the discovery of new molecules from natural sources, such as curcumin, has been reported for the treatment of fungal diseases. However, this drug has poor solubility in aqueous solvents and presents low bioavailability. Thus, the system was designed for a low viscosity precursor of a liquid crystal phase, and saliva leads a phase behaviour increasing the viscosity of system and the residence time in the mucosa and promotes antifungal activity Formulation composed of PPG-5-CETETH-20, oleic acid and water (30, 30, 40% w/w) denominated F. This formulation was diluted with artificial saliva at 10, 20 and 30% (w/v). These formulations were characterized by polarized light microscopy (PLM), mechanical behaviour, oscillatory rheology and performance studies on mucosa. In vitro studies were performed against a standard strain (ATTC 18804) or buccal isolated clinical strains for determinate the minimum inhibitory concentrations (MIC). PLM and Small-Angle X-ray Scattering (SAXS) revealed that formulation F is lamellar mesophase, whereas its dilution with artificial saliva changed the system to anisotropic hexagonal mesophase. Textural profiles show the increasing with the dilution of precursor system. Rheological measurements show that diluted systems exhibit elastic modulus values (G,) than viscous modulus (G,,) and it indicates more micro-structured system. Mucoadhesive force against excised porcine oesophageal mucosa showed that systems have properties mucoadhesive. Ex vivo retention studies on porcine oesophageal mucosa exhibited an increase of 5-fold and 3-fold in the retention of curcumin from F and F30, respectively. In vitro antifungal assay against Candida albicans revealed that curcumin-loaded systems were more potent against a standard strain (ATTC 18804) and buccal isolated strains compared with a curcumin solution. Hence, the physicochemical characterization, combined with ex vivo and in vitro studies, revealed that formulation designed could form a in situ gelling mucoadhesive with buccal retention of curcumin and the increase of its antifungal activity with great potential in the treatment of oral candidiasis.
Keywords: Buccal Administration; Candida albicans; Liquid Crystalline Systems; Mucoadhesive System; Surfactant Based-System